Valuation of Natural Resources - Maquieira V., Carlos (Estudios de Administración, 1995)
This article reviews the most important studies related to the problem of valuing investments on natural resources. We first consider some of the models developed in economics and then we focus on the most recent models which are based on a private evaluation perspective. Using the contingent claims analysis, the models are built on financial principles under uncertainty conditions.